An activist-holiness Kenneth Hagin? A case study of prosperity theology in the Philippines - Maltese, Giovanni (Peter Lang AG, 2015)
Abstract Prosperity theology and holiness theology are frequently regarded as irreconcilable antitheses in Pentecostal Studies and both as opposed to "structural" approaches to poverty alleviation.2 This is different in Dumaguete Philippines. Here, prosperity theology is holiness theology and it is oftentimes framed along issues that relate to the Filipino nation and society. Analyzing articulations on prosperity, this chapter will show how causes and solutions for poverty are debated among pastors and how they lead to different practices. Drawing on extensive field work (2009-2014) I argue that holiness theology became a means of rationalization vis-à-vis the failures of prosperity teachings to deliver on its prom ises. Providing a language for articulating moral critique of both, individuals and social con ditions as a whole, it leads to an alternative explanation for the failures of development in terms that include collective and structural sin. Accordingly, the confession and seed-faith principles, inherited from the Word-of-Faith-Movement are turned collective, which leads to different forms of social and political engagement as remedy for poverty.
CRIS-Team Scopus Importer:2024-03-27